Kutudaun (Hemiptera: Aphididae) pada gulma di sekitar lahan pertanian di Jawa Barat beserta kunci identifikasinya - Maharani, Yani; Hidayat, Purnama; Rauf, Aunu; Maryana, Nina (Jurnal Entomologi Indonesia, 2018)
Aphids (Hemiptera: Aphididae) are considered as one the most important pest in the world. Some species of aphids were reported as serious pests and plant virus vectors, especially on horticultural crops. Weeds in the agricultural area can serve as an alternative hosts for some aphids which are plant pests or plant virus vectors. The objective of this research was to identify aphid species of weeds in the agricultural production area in West Java and to provide the identification key. Aphids collection was done on the weeds in the agricultural fields in 9 districts of West Java. Aphids were collected from 13 species (5 families) of weeds. The identification of aphid was peformed based on the adult specimens. The research manased to come up with 12 species of aphid on weeds. Three of the 12 collected species were Epameibaphis frigidae (Oestlund), Metopolophium dirhodum (Walker), and Pseudaphis sijui (Eastop) has never been reported in West Java. Six species were known as vectors of plant viruses in agricultural crops. The most commonly found aphid species was Schizaphis graminum (Rondani) in the yard grass (Eleusine indica).